Results of transanal mesorectumectomy in patients with rectal cancer - A. O. Rasulov; Kh. E. Dzhumаbaev; V. M. Kulushev; Z. Z. Mamedli; N. A. Kozlov; S. S. Gordeev; A. B. Baychorov (Тазовая хирургия и онкология, 2017)
Objective: comparative analysis of specific perioperative features and pathological characteristics of the removed sample after laparoscopic total mesorectumectomy (Lap-TME) and transanal total mesorectumectomy (Ta-TME).Materials and methods. A prospective non-randomized controlled study was carried out from November 2013 until September 2016. Patients with сТ1–4aN0–2M0 cancer of low- or medium-ampullar section of rectum were enrolled.Results. 55 and 54 patients were included in the Ta-TME and Lap-TME groups respectively. Duration of surgery was 285 min (Ta-TME group) and 260 min (Lap-TME group); median volume of blood loss was less than 100 ml; duration of hospital stay after surgery was 7 days in both groups. 1 (1.8 %) patient from Ta-TME group and 3 (5.6 %) patients from the control group had conversion to open surgery (р = 0.223). Transanal removal of the sample was done in 53.7 % of the cases in Ta-TME group and 25.5 % of the cases in Lap-TME group (p = 0.008). Complications were registered in 27,3 and 24,1 % of the patients respectively (р = 0,436). 90.9 % of the patients from Ta-TME group had Grade 2–3 quality of mesorectumectomy, while in Lap-TME group this parameter was 85.2 % (p = 0.266). Circumferential resection margin damage was observed in 7.3 % of cases from Ta-TME group and 9.3 % of cases from Lap-TME group (p = 0.488).Conclusion. Ta-TME does not worsen short-term oncological results. Further randomized studies are required to identify those patients who would benefit from bottoms up mesorectumectomy.